TEACHING ENGLISH AS A SECOND LANGUAGE - Ibrokhimova Diyorakhon Mukhtorovna; Yuldasheva F.F (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article aims to give useful information and to show some tips for becoming a good foreign language teacher. And difficulties of language teaching are also briefly given.